Understanding the Theoretical Framework of Choreography in Bharatanatyam: An Overview - Bhavana, Sivayokan (Integrated Journal for Research in Arts and Humanities, 2022)
Bharatanatyam is one of the oldest classical dance forms which are in practice today. It has three divisions within itself: Nritham, Nrithyam, and Natyam. Nritham is the pure dance or rhythmic movement of the body, Nrithyam is the part of the dance that conveys emotions, and Natyam is the dramatic representation of dance. For any piece of dance, choreography is important. Choreography, being the art of designing dance, includes inventing or arranging movement and choosing dramatic structures to organize and present it to the audience. Effective choreography comes from the understanding of different elements of movement and the aspects of designing movements. Effective choreography is crucial not just for pieces of a traditional Bharatanatya repertoire, like a Varnam, Patham, or Thillana, but also for dance dramas. However, choreographing a dance drama slightly differs as it incorporates drama elements in addition to dance elements. This paper discusses the theories used in choreography and the elements and aspects that are important in the choreography of any item in a traditional Bharatanatya repertoire. It then discusses how these theories are used in the choreography of dance dramas. Further, this paper postulates that understanding the theoretical framework of choreography can contribute to creating visually compelling and harmonious strings of movements, by bridging the gap between the science behind the body movements and the artistic quality of such movements.